One Malaysia, under God, bipolar essays on society, schooling, and salvation - Azly Rahman (Strategic Information and Research Development Centre World Wise Books, 2015)
The book is a smorgasbord of commentaries on the poetics and politics of cultural life in a nation that is struggling to transcend its racialized structure to forge a cohesive and harmonious future. The word 'smorgasbord' may give the impression that what is presented in this book is simply a variety of 'dishes', hot and cold, familiar and exotic, all separate and distinct treats laid out on a buffet table. It is a smorgasbord with a difference: all the 'culinary delights' (read: commentaries) are laid out in an orderly manner with a story line that threads through the whole text. Organised around three main themes-society, schooling, and salvation-the commentaries offer rich food for thought and reflection and satisfy the intellectual and political appetite of anyone interested in Malaysian affairs and cultural politics in general....